722 Induction of metabolic shift from glycolysis to pentose phosphate pathway in human bladder cancer cells exposed to benzo[a]pyrene. (24th April 2018) - Verma, Nisha; Pink, Mario; Rettenmeier, Albert W; Schmitz-Spanke, Simone
Abstract : Introduction: Benzo[a]pyrene (B[a]P), a well-known polyaromatic hydrocarbon, is known for its lung carcinogenicity, however, its role in bladder cancer development is still discussed. The present investigations involves analysis of the shift in cellular metabolism that the bladder epithelia cells (RT4) undergo to sustain the hostile environment generated by B[a]P-induced toxicity. Methods: We applied the two-dimensional blue native SDS-PAGE (2D BN/SDS-PAGE) technique to elucidate the network of protein-protein interactions that regulate cellular metabolism. In order to analyse the effects of B[a]P-induced protein alterations at the metabolite level, untargeted metabolomic profiling of B[a]P-exposed cells was carried out by using gas chromatographic mass spectrometric analysis (GC-MS). Results: It appeared that B[a]P exposure led to a repression of enzymes (fructose-bisphosphate aldolase A, glucose-6-phosphate isomerase, lactate dehydrogenase) involved in glycolysis, and an up-regulation of proteins (glucose-6-phosphate 1-dehydrogenase, 6-phosphogluconolactonase) catalysing the pentose phosphate pathway and one carbon metabolism (10-formyltetrahydrofolate dehydrogenase, bifunctional purine biosynthesis protein). Untargeted metabolomics analysis revealed, lower concentration of glycolytic metabolites, as compared to glutamine, xylulose and fatty acids. The analysis of the glutathione and nucleotide content of the cells revealed a significant increase of these cofactors. Concomitantly, we did not observe any detectable increase in the production of ROS. Discussion: The study provides new insights into a B[a]P-induced shift in cellular metabolism towards processes involved in NADPH generation. B[a]P exposure causes oxidative DNA damage and hence cellular perturbations. To overcome these effects, the cells undergo a metabolic flux change from glycolysis to the pentose phosphate pathway. This shift leads to the generation of the redox cofactor NADPH that is essential for the activity of many antioxidant enzymes and intermediates necessary for the de novo generation of nucleotides (purine and pyrimidine) and for the normal functioning of the cells. The study provides preliminary indication of changes in cellular metabolism upon B[a]P exposure.